1996
DOI: 10.1002/art.1780390311
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric diagnoses in patients with fibromyalgia are related to health care–seeking behavior rather than to illness

Abstract: Objective. To compare the frequency of lifetime psychiatric disorders among 3 groups of subjects: patients with fibromyalgia syndrome (FMS) from a tertiary care setting, community residents with FMS who had not sought medical care for their FMS symptoms (' 'FMS nonpatients' '), and healthy controls. Fibromyalgia syndrome (FMS) is a relatively common, chronic musculoskeletal pain disorder of unknown cause that affects -15% of rheumatology clinic patients (1). The etiopathogenesis of FMS is not understood, but p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
124
1
22

Year Published

1996
1996
2003
2003

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 249 publications
(153 citation statements)
references
References 31 publications
3
124
1
22
Order By: Relevance
“…However, it is precisely the subjective perception of an event as emotionally stressful which has repeatedly been related to increased levels of health care utilization. Our findings are consistent with multiple sources of evidence indicating that perceived stressful life events and reports of emotional distress predict health care-seeking behavior in the general population as well as in patients with rheumatic diseases (10,15,23). Similarly, we have found that patients with FMS who are seen in tertiary care rheumatology practices exhibit a greater number of lifetime psychiatric diagnoses relative than did patients with no trauma (P = 0.0009).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…However, it is precisely the subjective perception of an event as emotionally stressful which has repeatedly been related to increased levels of health care utilization. Our findings are consistent with multiple sources of evidence indicating that perceived stressful life events and reports of emotional distress predict health care-seeking behavior in the general population as well as in patients with rheumatic diseases (10,15,23). Similarly, we have found that patients with FMS who are seen in tertiary care rheumatology practices exhibit a greater number of lifetime psychiatric diagnoses relative than did patients with no trauma (P = 0.0009).…”
Section: Discussionsupporting
confidence: 88%
“…Specifically, patients with emotional trauma reported significantly greater fatigue than did both patients with physical trauma and patients with no trauma ( P = 0.039 and P = 0.011, respectively). to nonpatients (15). Emotionally stressful events may enhance the perceived uncontrollability of symptoms, and thereby encourage persons to seek care from physicians as a means of modulating distress (2,25).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, we believe that 3 critical methodologic procedures may have compromised the external (i.e., generalizability) and internal validity of the study. This is a crucial issue because we cannot easily reconcile Bendtsen et al's conclusion that abnormal central neurosensory processing among FMS patients occurs only at "tender" muscles but not at "normal" muscles, with the reliable finding of generalized low pain thresholds in FMS patients at both tender and control points, which has been reported by us and by others (2,3). Thus, Bendtsen et al's methodologic procedures should be carefully examined before the conclusion of their study is accepted.…”
Section: To the Editormentioning
confidence: 71%